Numerical investigation of the effects of rail vibration absorbers on wear behaviour of rail surface. (March 2019) - Qian, WJ; Huang, ZQ; Ouyang, H; Chen, GX; Yang, HJ
Rail corrugation refers to the periodic wear of the top working surfaces of rails. This problem has plagued the railway industry over a hundred years. In the present paper, the effects of rail vibration absorbers on wear behaviour of the rail surface have been studied. The dynamic model of a wheel–rail–absorber system is established. The friction contact coupling between the wheel and the rail are fully considered in this model. A wear model, in which the mass loss of unit area in contact patch is proportional to frictional work per unit area between the wheel and the rail, is developed to analyse the wear behaviour of the rail surface. Numerical results show that the saturated creep force-induced self-excited vibration of the wheel–rail system can result in short pitch rail corrugation on the rail surface. The maximum wear depth occurs at the positions close to mid-span of each sleeper bay. After the installation of rail vibration absorbers, the formation of short pitch rail corrugation can be suppressed effectively, and the wear on the rail surface becomes uniform and the growth rate of rail corrugation reduces considerably. Increasing the connection damping between the absorber and the rail web is beneficial to preventing the formation of short pitch rail corrugation.